A Literasi Digital sebagai Fondasi Penguatan Learning Agility dan Adaptabilitas Karier dalam Pendidikan Vokasi: Tinjauan Literatur Sistematis - Ahmad Junaidi; Tuwoso; Marsono; Andika Bagus Nur Rahma Putra (Universitas Nahdlatul Ulama Blitar, 2026)
The rapid digital transformation driven by the Industrial Revolution 4.0 and Artificial Intelligence (AI) has fundamentally reshaped workforce competency requirements, requiring Technical and Vocational Education and Training (TVET) to prepare graduates with adaptive and future-oriented capabilities. This study aims to systematically synthesize empirical evidence regarding the relationships among digital literacy, learning agility, and career adaptability within the TVET context to support future workforce readiness. A Systematic Literature Review (SLR) was conducted using a seven-stage review protocol following the PRISMA framework. Relevant studies were identified from the Scopus, Web of Science, and ERIC databases, resulting in 12 eligible articles that met the predefined inclusion and exclusion criteria. The findings consistently demonstrate that digital literacy serves as the foundational competence that strengthens learning agility, which subsequently enhances career adaptability in rapidly changing labor markets. The synthesis further highlights the strategic roles of AI, micro-credentials, and adaptive learning platforms in fostering lifelong learning and workforce resilience. Unlike previous reviews that predominantly examined these concepts independently, this review provides an integrated synthesis explaining how digital literacy, learning agility, and career adaptability interact simultaneously within the TVET ecosystem. The findings offer practical implications for curriculum redesign, digital infrastructure investment, educator professional development, and stronger collaboration between educational institutions and industry to develop adaptive and sustainable future workforce competencies.